2023
DOI: 10.1038/s41893-023-01076-x
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical weeding enhances ecosystem multifunctionality and profit in industrial oil palm

Abstract: Oil palm is the most productive oil crop, but its high productivity is associated with conventional management (that is, high fertilization rates and herbicide application), causing deleterious environmental impacts. Using a 22 factorial experiment, we assessed the effects of conventional vs reduced (equal to nutrients removed by fruit harvest) fertilization rates and herbicide vs mechanical weeding on ecosystem functions, biodiversity and profitability. Analysing across multiple ecosystem functions, mechanica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 68 publications
0
9
0
Order By: Relevance
“…Adequate plantation management including the optimization of the N fertilization regime are therefore crucial to reduce the plantations' global warming potential. In the same oil palm plantation, it was shown that reducing fertilizer inputs, combined with mechanical weeding, promote biodiversity, ecosystem multifunctionality, maintain high yield and increase profit as compared to the conventional high fertilizer inputs with herbicide application (Iddris et al, 2023).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Adequate plantation management including the optimization of the N fertilization regime are therefore crucial to reduce the plantations' global warming potential. In the same oil palm plantation, it was shown that reducing fertilizer inputs, combined with mechanical weeding, promote biodiversity, ecosystem multifunctionality, maintain high yield and increase profit as compared to the conventional high fertilizer inputs with herbicide application (Iddris et al, 2023).…”
Section: Discussionmentioning
confidence: 99%
“…The oil palm plantation is fertilized manually with “Pamafert” nitrogen‐phosphorus‐potassium granular (174.4 kg N, 47.6 kg P and 190.6 kg K ha −1 year −1 ), and dolomite (426 kg ha −1 year −1 , based on average soil pH of 5.6) in top‐dress application (Darras et al, 2019; Iddris et al, 2023; Meijide et al, 2020). According to the plantation owner, fertilization follows a defined routine and time schedule in which the plantation is divided into management micro‐divisions.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…has resulted in alarming losses of biodiversity and ecosystem functions 36 . Therefore, to safeguard multifaceted tropical diversity, it is imperative to prioritize the conservation of remaining forests 7 , improve conventional management practices 8 , and restore human-modified landscapes aiming at biodiversity-friendly habitats that can preserve tropical biodiversity outside of protected areas 9,10 .…”
Section: Main Textmentioning
confidence: 99%